Ethnocentric Trends in Sociology: A Critical View (American Journal of Islam and Society, 1994)
Sociology was developed in the western intellectual ethos within adistinct sociopolitical milieu rooted in a postrevolutionary Europecharacterized by new tmds of thought that represented serious and sharpteLtctions to the prevailing social situation. Social thinkem of the periodexpressed an intense desire to develop a new science of Society that, onceequipped with adequate methods and theoretical constmcts, could be usedto study and better understand society and social phenomena. This newtool would then be used to analyze how the construction and teconstructionof society could be carried out to ameliorate the lot of people.During the sixteenth to eighteenth centuries, European society passedthrough a tumultuous state and witnessed drastic changes in its Social andintellectual fabrics. The expansion of trade in the sevenknth century ledto the crumbling of the economic order and the emergence of its newmastem: guilds and charted corporations. The eighteenth century replacedthis system with that of free labor and competitive production. Theemergence of large-scale industries structured the economic organizationanew and accelerated both pduction and profit. Competition fotcedindustries to develop new technology in order to increase production andproduce better quality goods. Markets were explod and expanded, andtrade was encouraged. This economic mrganization affected the patternof social life, as the ensuing population shift from the rural to urban areasaltered the extant family structure. In addition, the rule of law began tobe considered necessary for the smooth functioning of the new economicorder. These developments gradually transformed the feudal order and thetransitory mercantile order into a capitalist economic system that created ...